Functional Characterization of the Atpase-Like Activity Displayed by a Catalytic Amyloid - Diaz-Espinoza, R (Elsevier B.V., 2021)
Background: Amyloids are highly ordered polypeptide aggregates stabilized by a beta-sheet structural core. Though classically associated to pathology, reports on novel functional roles of these proteins have increasingly emerged in the past decade. Moreover, the recent discovery that amyloids formed with rationally designed small peptides can exhibit catalytic reactivity has opened up new opportunities in both biology and biotechnology. The observed activities typically require the binding of divalent metals, giving rise to active metal-amyloid complexes. Methods: Peptide (SDIDVFI) was aggregated in vitro. The structure of the self-assembled species was analyzed using fluorescence, transmission electron microscopy, circular dichroism and computational modeling. A kinetic characterization of the emerging catalytic activity was performed. Results: The peptide self-assembled into canonical amyloids that exhibited catalytic activity towards hydrolysis of the phosphoanhydride bonds of adenosine triphosphate (ATP), partially mimicking an ATPase-like enzyme. Both amyloid formation and activity are shown to depend on manganese (Mn2+) binding. The activity was not restricted to ATP but also affected all other ribonucleotides (GTP, CTP and UTP). Peptides carrying a single aspartate exhibited a similar activity. Conclusions: The phosphoanhydride bonds appear as the main specificity target of the Mn2+-amyloid complex. A single aspartate per peptide is sufficient to enable the hydrolytic activity. General significance: Catalytic amyloids are shown for the first time to catalyze the hydrolysis of all four ribonucleotides. Our results should contribute towards understanding the biological implications of amyloid-mediated reactivity as well as in the design of future catalytic amyloids for biotechnological applications. © 2020 Elsevier B.V.